THE ROLE OF THE EXTERNAL AUDITOR IN LIMITING CREATIVE ACCOUNTING PRACTICES IN FINANCIAL STATEMENTS ANALYTICAL STUDY OF IRAQI JOINT STOCK COMPANIES - Abbas Fadel Chiyad (Scholars Digest Publishing, 2023)
This study aims to identify the concept and definition of creative accounting and the role of external auditors to discover the ways and methods of creative accounting used in financial statements by the departments of joint stock companies operating in the Iraqi market, To achieve the objectives of this study and to test its hypothesis, the descriptive analytical approach was followed, where the primary data was collected through a questionnaire distributed to (40) external auditors practicing the profession of external auditor in auditing offices and companies in Iraq, who were chosen randomly, The questionnaire was distributed to them through the Iraqi Association of Certified Public Accountants (a non-governmental organization) through a visit to audit offices and companies practicing the profession of external audit and licensed during 2022, As well as company employees and academics with specialization. the researcher designed a questionnaire that included (14) items to collect the primary information from the study sample and analyze it using the statistical program (SPSS), using arithmetic averages, standard deviations, and coefficient of variation, as well as percentages and the T-test. The study reached a set of results, including the commitment of external auditors to apply the necessary procedures and tests in the elements of the financial statements, which helps them in limiting creative accounting practices in financial deception by exploiting the flexibility given in accounting policies and laws and the freedom to choose between alternatives. In addition to the availability of educational qualifications and professional experience, this enhances their ability to discover creative accounting practices in financial statements. The study concluded with several recommendations, the most important of which is that professional associations hold seminars and educational media programs for their preachers related to clarifying the impact of creative accounting practices on the accounting and auditing professions and educating users of financial statements in general, and investors and lenders in particular of the effects of those practices on their economic decisions.
Keywords: Creative accounting, auditor, auditing, financial statements, corporate companies.